2018
DOI: 10.1007/s00276-018-2066-5
|View full text |Cite
|
Sign up to set email alerts
|

Focus on anatomical aspects of soft tissue coverage options in elbow reconstruction: an updating review

Abstract: The anatomical basis of the flap's harvesting and the possibilities of elbow coverage are discussed through the selected articles. The different indications according to the areas of soft tissues defects are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Gandolfi et al reported use of propeller flaps based on radial collateral artery perforator and posterior ulnar recurrent artery perforator for elbow defect coverage. 7 Propeller flaps in our study were based on perforators from RRA similar to that reported by Panse and Sahasrabudhe. 14 Islanded perforator flaps based on PURA for elbow coverage resulted in better donor site cosmesis as reported by Mateev et al 15 The PURA flap provides a large skin paddle extending proximally up to midarm and comprising almost the entire medial circumference of the arm enabling coverage of complex moderate to large laterally located defects.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Gandolfi et al reported use of propeller flaps based on radial collateral artery perforator and posterior ulnar recurrent artery perforator for elbow defect coverage. 7 Propeller flaps in our study were based on perforators from RRA similar to that reported by Panse and Sahasrabudhe. 14 Islanded perforator flaps based on PURA for elbow coverage resulted in better donor site cosmesis as reported by Mateev et al 15 The PURA flap provides a large skin paddle extending proximally up to midarm and comprising almost the entire medial circumference of the arm enabling coverage of complex moderate to large laterally located defects.…”
Section: Discussionsupporting
confidence: 62%
“…Gandolfi et al reported use of propeller flaps based on radial collateral artery perforator and posterior ulnar recurrent artery perforator for elbow defect coverage. 7 Propeller flaps in our study were based on perforators from RRA similar to that reported by Panse and Sahasrabudhe. 14 Islanded perforator flaps based on PURA for elbow coverage resulted in better donor site cosmesis as reported by Mateev et al 15…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Coverage options broadly include primary closure, local fasciocutaneous flaps (e.g., medial or lateral arm/forearm flaps), local muscular flaps (e.g., anconeus flap, brachioradialis flap), regional pedicled flaps (e.g., latissimus dorsi flap, thoracodorsal perforator flap), distant pedicled flaps (e.g., paraumbilical perforator flaps), and free tissue transfer (Elhassan et al, 2011; Gutwein et al, 2015; Kahramangil et al, 2022; Rogachefsky et al, 2002; Stevanovic & Sharpe, 2013; Tung et al, 1997; Türegün et al, 2005; Zampeli et al, 2019). In addition to patient comorbidities and other patient selection factors that are predictive of successful reconstruction, size of the defect, etiology of the wound, and the presence of concomitant bony and neurovascular injury are important considerations when selecting the optimal method for achieving definitive soft tissue coverage (Adkinson & Chung, 2014; Gandolfi et al, 2018; Jensen & Moran, 2008; Kelley & Chung, 2015; Patel & Higgins, 2013; Stevanovic & Sharpe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The posterior elbow features thickened skin to facilitate adequate support given the load‐bearing nature of the joint. At the same time, native elbow soft tissue is highly pliable to facilitate functional range of motion (Chapleau et al, 2013; Gandolfi et al, 2018; Kelley & Chung, 2015).…”
Section: Introductionmentioning
confidence: 99%